Unveiling novel serum biomarkers in intrahepatic cholangiocarcinoma: a pilot proteomic exploration - Mocan, Lavinia Patricia; Grapa, Cristiana; Crăciun, Rareș; Pralea, Ioana Ecaterina; Uifălean, Alina; Soporan, Andreea Maria; Mureșan, Ximena Maria; Iacobescu, Maria; Al Hajjar, Nadim; Mihu, Carmen Mihaela; Spârchez, Zeno; Mocan, Tudor; et al. (Frontiers in Pharmacology, 2024)
Recent advancements in proteomics have shown promise in identifying biomarkers for various cancers. Our study is the first to compare the serum proteomes of intrahepatic cholangiocarcinoma (iCCA) with cirrhosis (CIR), primary sclerosing cholangitis (PSC), and hepatocellular carcinoma (HCC), aiming to identify a proteomic signature that can effectively distinguish among these conditions. Utilizing high-throughput mass spectrometry on serum samples, we identified 845 proteins, of which 646 were suitable for further analysis. Unique clustering patterns were observed among the five groups, with significant proteomic differences. Our key findings include: S100 calcium-binding protein A9 (S100A9) and haptoglobin (HP) were more abundant in iCCA, while intercellular adhesion molecule 2 (ICAM2) was higher in HCC. Serum amyloid A1 (SAA1) and A4 (SAA4) emerged as potential biomarkers, with SAA1 significantly different in the iCCA vs. healthy controls (HC) comparison, and SAA4 in the HCC vs. HC comparison. Elevated levels of vascular cell adhesion molecule 1 (VCAM-1) in HCC suggested its potential as a differentiation and diagnostic marker. Angiopoietin-1 receptor (TEK) also showed discriminatory and diagnostic potential in HCC. ELISA validation corroborated mass spectrometry findings. Our study underscores the potential of proteomic profiling in distinguishing iCCA from other liver conditions and highlights the need for further validation to establish robust diagnostic biomarkers.